COMPONENT COMPOSITION OF ESSENTIAL OIL FROM SPECIES OF GENUS NEPETA L. - V. D. Rabotyagov; Yu. V. Aksenov (Фармация и фармакология (Пятигорск), 2015)
Data about content and component composition of essential oil of six species from genus Nepeta L. in the condition of South coast of the Crimea have been given for the first time. We have identified from 16 to 21 components. Specimen with cytronellol content up to 58,42% and geranilacetat content up to 14,60% have been selected.